Lessons learned from community approaches to COVID-19 prevention: a qualitative study with transgender adults in the United States - Robynn Ashenden; Eunice Okumu; Dee Adams; Carter Brown; Marissa Miller; Sari Reisner; Andrea L. Wirtz; Tonia Poteat (Community Health Equity Research & Policy, 2026)
The COVID-19 pandemic prompted widespread public health measures, including non-pharmaceutical (NPIs) and pharmaceutical interventions (PIs). This study explores the prevention strategies adopted by transgender individuals and examines how structural and attitudinal factors shaped their uptake within trans-specific healthcare and social contexts. As part of the LITE Connect mixed-methods study (N = 2,092), 30 participants engaged in qualitative, semi-structured interviews between October 2021 and June 2022. Content analysis identified the use of NPIs such as masking, sanitizing, social distancing, and testing, as well as the PI of vaccination. Structural and attitudinal barriers influenced these strategies, including healthcare discrimination, limited testing accessibility, and vaccine hesitancy driven by mistrust and concerns about side effects. Vaccine uptake was facilitated by access to trusted health information and alternative vaccine delivery methods. Findings emphasize the importance of culturally competent healthcare, inclusive public health policies, and community-driven approaches to improving prevention efforts. Addressing both structural and attitudinal barriers is essential to reducing inequities and ensuring equitable access to effective health interventions in future pandemics, particularly for marginalized communities.